Pengembangan dan Pelatihan LMS Interaktif Berbasis Game Untuk Literasi Numerasi Siswa SD Negeri 067240 Medan - Dedi Kiswanto; Melly Br Bangun; Safrida Napitupulu (STMIK Royal, 2026)
Abstract: The literacy and numeracy achievements of elementary school students in Indonesia still face various challenges, despite showing an upward trend based on the results of the National Assessment. One cause is the implementation of conventional and less interactive learning models. This community service activity aims to develop and train the use of the interactive Learning Management System (LMS) kelaspetualang.com integrated with Scratch-based educational games to support literacy and numeracy learning at SD Negeri 067240 Medan. The implementation method used an interactive workshop based on practice-based learning that included needs analysis, material development, training, implementation, mentoring, and evaluation. The activity participants consisted of 20 teachers. The evaluation was conducted using a 1–5 Likert scale questionnaire to measure understanding, interest, and effectiveness of the activity. The results of the activity showed that 18 teachers successfully developed and uploaded game-based teaching materials to the LMS, while two teachers experienced technical difficulties with the device. The evaluation results showed a very good level of understanding and enthusiasm, especially regarding interest in developing game-based learning media, although further mentoring is still needed on technical aspects. This activity has been proven to improve teachers' digital competence and literacy and has the potential to enrich literacy and numeracy learning in an innovative way. Keywords: educational; games; scratch; literacy; numeracy Abstrak: Capaian literasi dan numerasi siswa sekolah dasar di Indonesia masih menghadapi berbagai tantangan, meskipun menunjukkan tren peningkatan berdasarkan hasil Asesmen Nasional. Salah satu penyebabnya adalah penerapan model pembelajaran yang masih konvensional dan kurang interaktif. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk mengembangkan dan melatih pemanfaatan Learning Management System (LMS) interaktif kelaspetualang.com yang terintegrasi dengan game edukatif berbasis Scratch guna mendukung pembelajaran literasi dan numerasi di SD Negeri 067240 Medan. Metode pelaksanaan menggunakan workshop interaktif berbasis practice-based learning yang meliputi analisis kebutuhan, pengembangan materi, pelatihan, implementasi, pendampingan, dan evaluasi. Peserta kegiatan terdiri atas 20 guru. Evaluasi dilakukan menggunakan kuesioner skala Likert 1–5 untuk mengukur pemahaman, minat, dan efektivitas kegiatan. Hasil kegiatan menunjukkan bahwa 18 guru berhasil mengembangkan dan mengunggah materi ajar berbasis game ke dalam LMS, sementara dua guru mengalami kendala teknis perangkat. Hasil evaluasi menunjukkan tingkat pemahaman dan antusiasme yang sangat baik, terutama pada minat pengembangan media pembelajaran berbasis game, meskipun masih diperlukan pendampingan lanjutan pada aspek teknis. Kegiatan ini terbukti meningkatkan kompetensi dan literasi digital guru serta berpotensi memperkaya pembelajaran literasi dan numerasi secara inovatif. Kata kunci: pendidikan; permainan; Scratch; literasi; numerasi.